Secretariat [videorecording (DVD)] - Wallace, Randall, 1949-; Lane, Diane; Malkovich, John; Walsh, Dylan; Cromwell, James; Connolly, Kevin, 1974-; Glenn, Scott, 1942- (Walt Disney Studios Home Entertainment, 2011)
Behind every legend lies an impossible dream. Witness the spectacular journey of an incredible horse named Secretariat and the moving story of his unlikely owner, a housewife who risked everything to make him a champion.